Ocular biometric parameters of mild hyperopia to mild myopia children aged 6–14 years from Wenzhou optometry center: A cross-sectional study - Liu, Weiqin; Liu, Weishai; Wang, Chenxiao (Frontiers in medicine, 2022)
Myopia is the most common visual disorder in school-aged children and adolescents worldwide. This study aimed to explore the ocular biometric characteristics of children aged 6-14 years from the Wenzhou optometry center and to determine the relationship between spherical equivalent refraction (SER) and macular pigment optical density (MPOD).IntroductionMyopia is the most common visual disorder in school-aged children and adolescents worldwide. This study aimed to explore the ocular biometric characteristics of children aged 6-14 years from the Wenzhou optometry center and to determine the relationship between spherical equivalent refraction (SER) and macular pigment optical density (MPOD).Participants underwent a full-scale ophthalmic examination anteriorly and posteriorly. Relevant parameters were documented, such as axial length (AL), anterior chamber depth (ACD), SER and lens thickness (LT), corneal curvature radius (CCR), and MPOD. Lens power (LP) was calculated using Bennett's formula. Shapiro-Wilk tests and histograms were used to check the normality of the distribution of refractive and ocular biometric parameters. Scatter diagrams were adopted to analyze the relationships between refraction and parameters of ocular biometry. Multiple linear regression models were employed to fit the associated factors of AL, AL/CCR, and LP.Subjects and methodsParticipants underwent a full-scale ophthalmic examination anteriorly and posteriorly. Relevant parameters were documented, such as axial length (AL), anterior chamber depth (ACD), SER and lens thickness (LT), corneal curvature radius (CCR), and MPOD. Lens power (LP) was calculated using Bennett's formula. Shapiro-Wilk tests and histograms were used to check the normality of the distribution of refractive and ocular biometric parameters. Scatter diagrams were adopted to analyze the relationships between refraction and parameters of ocular biometry. Multiple linear regression models were employed to fit the associated factors of AL, AL/CCR, and LP.A total of 902 mild hyperopia to mild myopia (+3.00 D ≤ SE ≤ -3.00 D) children aged 6-14 years were included. The mean age of participants was 10.03 ± 2.47 years, and the prevalence of mild hyperopia, emmetropia, and myopia was 5.65, 27.05, and 67.30%, respectively. The prevalence of mild myopia increased from 30.53% at 6 years of age to 93.62% at 14 years of age. Overall, AL, ACD, and AL/CCR increased, but LP declined from 6 to 14 years of age, whereas CCR and MPOD remained stable. An increase of 1 mm in AL was associated with -0.69 D of myopic change. A unit increase in AL/CCR was associated with -7.87 D in SER. As for the SER variance, AL explained 30.5% and AL/CCR explained 51.1%, whereas AL/CCR and LP accounted for 59.2%.ResultsA total of 902 mild hyperopia to mild myopia (+3.00 D ≤ SE ≤ -3.00 D) children aged 6-14 years were included. The mean age of participants was 10.03 ± 2.47 years, and the prevalence of mild hyperopia, emmetropia, and myopia was 5.65, 27.05, and 67.30%, respectively. The prevalence of mild myopia increased from 30.53% at 6 years of age to 93.62% at 14 years of age. Overall, AL, ACD, and AL/CCR increased, but LP declined from 6 to 14 years of age, whereas CCR and MPOD remained stable. An increase of 1 mm in AL was associated with -0.69 D of myopic change. A unit increase in AL/CCR was associated with -7.87 D in SER. As for the SER variance, AL explained 30.5% and AL/CCR explained 51.1%, whereas AL/CCR and LP accounted for 59.2%.In this work, we have studied the distributions of ocular biometric characteristics of mild hyperopia to mild myopia children from the perspective of an optometry center rather than a sampling survey. In addition, we found that children from the optometry center had a slower progression toward myopia than those from previous sampling surveys, which was an informative finding for future myopia prevention. In addition, we have made a correlation analysis between the macular pigment optical density and spherical equivalent refraction. Though, no correlation was found.DiscussionIn this work, we have studied the distributions of ocular biometric characteristics of mild hyperopia to mild myopia children from the perspective of an optometry center rather than a sampling survey. In addition, we found that children from the optometry center had a slower progression toward myopia than those from previous sampling surveys, which was an informative finding for future myopia prevention. In addition, we have made a correlation analysis between the macular pigment optical density and spherical equivalent refraction. Though, no correlation was found.